2017
DOI: 10.4103/ijpvm.ijpvm_375_16
|View full text |Cite
|
Sign up to set email alerts
|

Is cost of medication for quit smoking important for smokers, experience of using champix in Iranian Smoking Cessation Program 2016

Abstract: Background:Providing smoking cessation services are special importance to tobacco control programs. To date, Champix is a new expensive medication for smoking cessation available nationally. Champix has both agonist and antagonist activities and can reduce nicotine dependence and withdrawal symptoms. The purpose of this study was to evaluate the duration of using Champix based on its cost.Methods:This quasi-experimental study was conducted with smokers presenting to the Tanaffos Smoking Cessation Clinic in Teh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…However, in univariate analysis the FP was also found to increase the treatment adherence, so there is a chance that cost does play a role in early treatment cessation. Medication cost was found by Iranian researchers 18 to have an effect on varenicline users. Also, in the same study they found higher quit rates in the group that used varenicline over 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…However, in univariate analysis the FP was also found to increase the treatment adherence, so there is a chance that cost does play a role in early treatment cessation. Medication cost was found by Iranian researchers 18 to have an effect on varenicline users. Also, in the same study they found higher quit rates in the group that used varenicline over 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the evidence also suggests that varenicline used in this way would be acceptable to stakeholders ( 138 141 ). Although uptake of varenicline is low, people prefer pharmacotherapy options if they are of higher efficacy, have less-frequent side effects, and prevent weight gain ( 40 43 , 138 , 142 ). Cost concerns become less important in the presence of improved efficacy and safety.…”
Section: Questions and Recommendationsmentioning
confidence: 99%
“…The outcomes and aims of the included studies are summarized in Table 3. The most commonly reported outcome was the quit rate (n=18) 36,37,40,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] , followed by cessation rate (n=8) 39,41,[56][57][58][59][60][61] , sustained abstinence (n=1) 35 , fail to quit (n=1) 62 , cessation survival rate (n=1) 38 , and success rate (n=1) 35 . The majority of studies utilized a self-reported questionnaire to estimate quit rates, while some others used the carbon monoxide breath test to determine quitting state (n=19) 35-37,39-41,43,44,46-48,50-53, 55-57,59 .…”
Section: Outcomes Of the Tc Programsmentioning
confidence: 99%
“…For example, factors found to be associated with reduced effectiveness include individual withdrawal symptoms 39,45,47,57,63 , high nicotine dependence rate 36,38,43,49,52,60,62,63 , poor knowledge on how to quit 45 , change in attitudes and behaviors 43,56 , stress 47,48 , number of cigarettes smoked per day 62,63 , inability to afford higher priced medications 49,50,62 , and concern about gaining weight 51,63 . Other individual factors that were found to be associated with effective TC programs included older age 51,62 , female gender 61 , knowledge on the benefits of tobacco cessation 35,59 , health issues 41,47,53,54,59,[61][62][63] , higher education level 48,54 , religious beliefs 59 , and adherence to treatment 51 .…”
Section: Individual Factorsmentioning
confidence: 99%